Kinetic Viability Assays Using DRAQ7 Probe. Issue 1 (15th July 2013) - Wlodkowic, Donald; Akagi, Jin; Dobrucki, Jurek; Errington, Rachel; Smith, Paul J; Takeda, Kazuo; Darzynkiewicz, Zbigniew
Abstract: Cell death within cell populations is a stochastic process where cell‐to‐cell variation in temporal progression through the various stages of cell death arises from asynchrony of subtle fluctuations in the signaling pathways. Most cell death assays rely on detection of the specific marker of cell demise at the end‐point of cell culturing. Such an approach cannot account for the asynchrony and the stochastic nature of cell response to the death‐inducing signal. There is a need therefore for rapid and high‐throughput bioassays capable of continuously tracking viability of individual cells from the time of encountering a stress signal up to final stages of their demise. In this context, a new anthracycline derivative, DRAQ7, is gaining increasing interest as an easy‐to‐use marker capable of long‐term monitoring of cell death in real‐time. This novel probe neither penetrates the plasma membrane of living cells nor does it affect the cells' susceptibility to the death‐inducing agents. However, when the membrane integrity is compromised, DRAQ7 enters cells undergoing demise and binds readily to nuclear DNA to report cell death. Here, we provide three sets of protocols for viability assays using DRAQ7 probe. The first protocol describes the innovative use of single‐color DRAQ7 real‐time assay to dynamically track cell viability. The second protocol outlines a simplified end‐point DRAQ7 staining approach. The final protocol highlights the real‐time and multiparametric apoptosis assay utilizing DRAQ7 dye concurrently with tetramethylrhodamine methyl ester (TMRM), the mitochondrial trans‐membrane electrochemical potential (ΔΨm) sensing probe. Curr. Protoc. Cytom . 65:9.41.1‐9.41.8. © 2013 by John Wiley & Sons, Inc.